Tickborne Colpodella Species Infections: Time for a New Integrated Approach to Understand Transmission and Pathogenicity - Tobili Y. Sam-Yellowe; Trinity Nims; Sona Qaderi; Mary M. Asraf (Zoonotic Diseases)
Colpodella species are free-living predatory protists that prey on algae, ciliates and bodonids using myzocytosis. Colpodella species have been reported in human and animal infections. Polymerase chain reaction (PCR) using primers targeting 18S rRNA genes of Cryptosporidium and piroplasms have identified Colpodella species in arthropods, host blood and feces, demonstrating the phylogenetic closeness of Colpodella species to the apicomplexa. However, in human, animal and arthropod hosts, the life cycle stages of Colpodella are unknown. In this literature review, we provide an overview of the widespread occurrence of Colpodella species in ticks, and pathogenicity in humans and animals. We discuss methods for culture and microscopy that can aid diagnosis. Phylogenetic tree analysis of Colpodella species identified using 18S rRNA demonstrates that the Colpodella species identified in different geographic regions represent different species and strains that may impact virulence and zoonotic transmission. There is a pressing need to culture Colpodella species, and to stain cells for morphological identification. This will aid molecular investigations aimed at identifying molecular markers of Colpodella spp. facilitating transmission, survival and pathogenesis in hosts, and will determine which species and strains to prioritize for the risk of zoonotic infections to humans and for infections in animals.